2005
DOI: 10.1038/nm1214
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-related growth factor antagonizes obesity and insulin resistance

Abstract: Angiopoietin-related growth factor (AGF), a member of the angiopoietin-like protein (Angptl) family, is secreted predominantly from the liver into the systemic circulation. Here, we show that most (>80%) of the AGF-deficient mice die at about embryonic day 13, whereas the surviving AGF-deficient mice develop marked obesity, lipid accumulation in skeletal muscle and liver, and insulin resistance accompanied by reduced energy expenditure relative to controls. In parallel, mice with targeted activation of AGF sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
189
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(196 citation statements)
references
References 39 publications
4
189
3
Order By: Relevance
“…Although Oike et al showed that Angptl6 is involved in fat metabolism and may counteract obesity in mice [14], we detected no significant association between ANGPTL6 polymorphisms and body-weight-related variables in the French MONICA sample. This was not because of a lack of power as, even when considering the most rare allele (frequency 0.09), we would have detected a 0.7 kg/m 2 difference in mean BMI in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although Oike et al showed that Angptl6 is involved in fat metabolism and may counteract obesity in mice [14], we detected no significant association between ANGPTL6 polymorphisms and body-weight-related variables in the French MONICA sample. This was not because of a lack of power as, even when considering the most rare allele (frequency 0.09), we would have detected a 0.7 kg/m 2 difference in mean BMI in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, our findings could be consistent with a physiological role of Angptl6 in terms of insulin sensitivity and glucose metabolism as reported by Oike et al in transgenic mice [14]. Also, it has recently been shown that Angptl6 inhibits glucose production in rat hepatocytes by preventing expression of glucose-6-phosphatase, a key enzyme in gluconeogenesis [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1,9,[15][16][17][18][19] Whereas angiopoietins act via the Tie2 receptor tyrosine kinase, the signaling of which regulates vascular stabilization and remodeling, Angptls do not bind to either Tie2 or the related Tie1 receptor, suggesting that these orphan ligands function differently from angiopoietins. Although several studies show that Angptls potently regulate angiogenesis, 11,20 as do angiopoietins, some Angptls also possess pleiotropic activities other than angiogenesis, such as inhibition of lipoprotein lipase and endothelial lipase, 19,20 augmentation of energy expenditure, 19,21 and induction of inflammation. 22 Lifestyle changes in developed and developing countries, such as inactivity and overnutrition, have lead to the recent increase in the incidence of obesity, which is creating an exploding medical and social problem.…”
mentioning
confidence: 99%